Experimental Models to Study Podocyte Biology: Stock-Taking the Toolbox of Glomerular Research - Henning Hagmann; Paul T. Brinkkoetter (Frontiers Media S.A., 2018)
Diseases affecting the glomeruli of the kidney, the renal filtration units, are a leading cause of chronic kidney disease and end-stage renal failure. Despite recent advances in the understanding of glomerular biology, treatment of these disorders has remained extraordinarily challenging in many cases. The use of experimental models has proven invaluable to study renal, and in particular, glomerular biology and disease. Over the past 15 years, studies identified different and very distinct pathogenic mechanisms that result in damage, loss of glomerular visceral epithelial cells (podocytes) and progressive renal disease. However, animal studies and, in particular, mouse studies are often protracted and cumbersome due to the long reproductive cycle and high keeping costs. Transgenic and heterologous expression models have been speeded-up by novel gene editing techniques, yet they still take months. In addition, given the complex cellular biology of the filtration barrier, certain questions may not be directly addressed using mouse models due to the limited accessibility of podocytes for analysis and imaging. In this review, we will describe alternative models to study podocyte biology experimentally. We specifically discuss current podocyte cell culture models, their role in experimental strategies to analyze pathophysiologic mechanisms as well as limitations with regard to transferability of results. We introduce current models in Caenorhabditis elegans, Drosophila melanogaster, and Danio rerio that allow for analysis of protein interactions, and principle signaling pathways in functional biological structures, and enable high-throughput transgenic expression or compound screens in multicellular organisms.